2022
DOI: 10.3390/rs14040951
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Hail Damage in Crops Using Sentinel-2 Imagery

Abstract: Hailstorms are a frequent natural weather disaster in the Canadian Prairies that can cause catastrophic damage to field crops. Assessment of damage for insurance claims requires insurance inspectors to visit individual fields and estimate damage on individual plants. This study computes temporal profiles and estimates the severity of hail damage to crops in 54 fields through the temporal analysis of vegetation indices calculated from Sentinel-2 images. The damage estimation accuracy of eight vegetative indices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 38 publications
0
5
0
1
Order By: Relevance
“…However, this method cannot analyze several other crops like wheat, soybeans, and sugarcane. Ha et al (2022) established crop losses due to hail disasters with the sentimental-2 imagery technique. This study examined canola, wheat, and lentil crops in the Canadian region for hail damage.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this method cannot analyze several other crops like wheat, soybeans, and sugarcane. Ha et al (2022) established crop losses due to hail disasters with the sentimental-2 imagery technique. This study examined canola, wheat, and lentil crops in the Canadian region for hail damage.…”
Section: Related Workmentioning
confidence: 99%
“…Ha et al (2022) established crop losses due to hail disasters with the sentimental‐2 imagery technique. This study examined canola, wheat, and lentil crops in the Canadian region for hail damage.…”
Section: Related Workmentioning
confidence: 99%
“…Additionally, given the labor‐intensive task of assessing crop damage on the ground, other areas of future research should include the study of technologies to help rapidly and efficiently assess the damage in the crop—for example, crop models, satellite imagery, remote sensing (e.g., normalized difference vegetation index, NDVI), unmanned aerial vehicles, radar‐derived information for estimating crop stands, defoliation levels, and yield losses in affected fields. Although some of these efforts have been established recently (Bell & Molthan, 2016; Bell et al., 2020; Erda et al., 2012; Ha et al., 2022; Zhou et al., 2016), major limitations remain. These include reliable data sources, time for model development, model calibrations, and model validations, which at first are labor intensive and have other limitations such as technology costs, cloud coverage, surface variability (e.g., soil moisture, crop maturity, weeds presence), and dissecting crop damage from hail compared to other potential causes (e.g., insect defoliation).…”
Section: Hail/defoliation Damagementioning
confidence: 99%
“…'Canola'), and lentil (Lens culinaris Medik. ; Ha et al, 2022). Crop producers surveyed indicated that they perceive wheat is more sensitive than corn (Zea mays L.) to hail damage due to its smaller seed and head size (Childs et al, 2020).…”
mentioning
confidence: 99%